Crack Width Analysis of Reinforced Concrete Using FBG Sensor - Lili Wang; Jun Song; Yaozhang Sai; Honggang Wang (IEEE Photonics Journal)
According to the reflection behavior of the fiber Bragg grating, the monitoring method of reinforced concrete was presented in this paper. A postprocessing method to extract crack openings from a three-dimension finite element computation was proposed. The three-axial stresses of the FBG were extracted also from the same finite element computation, and then, were converted as a wavelength deformation of the FBG reflected spectrum. The three-dimension computation result of crack width versus the FBG spectrum deformation was investigated using laboratory experiments. The results showed that the numerical values approximated the experimental ones.